2015
DOI: 10.1007/s12134-015-0427-z
|View full text |Cite
|
Sign up to set email alerts
|

Labor Exploitation and Health Inequities Among Market Migrants: A Political Economy Perspective

Abstract: Previous discourses have recognized institutionalized forms of racism and pointed to structural violence embedded in Canadian policies, institutions, and labor markets. However, there is limited connection of these experiences to health. This paper theorizes a novel connection of health inequities experienced by racialized and immigrant peoples in Canada as a result of globalization and market liberalism. Beginning with a brief historical overview of the slave trade and indentured workers' experiences, it is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Canadian research suggests that (im)migrants, racialized populations, and women are vulnerable to poverty, illness, and diseases related to low income, psycho-social/ chronic stress, and socioeconomic status disparities ( [8,14,15,28,29,32,33,41,47,48]). The literature also shows that racialized and immigrant workers are vulnerable to both acute and chronic health problems because of structural issues in the labour market [11,12,48] that lead to major health risks such as work-related accidents or illness, mental stress, as well as income inequalities and health inequities [4,8,15,16,42,45,48,49,52]. Accordingly, it is imperative that these groups are targeted in order to reduce health inequities.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian research suggests that (im)migrants, racialized populations, and women are vulnerable to poverty, illness, and diseases related to low income, psycho-social/ chronic stress, and socioeconomic status disparities ( [8,14,15,28,29,32,33,41,47,48]). The literature also shows that racialized and immigrant workers are vulnerable to both acute and chronic health problems because of structural issues in the labour market [11,12,48] that lead to major health risks such as work-related accidents or illness, mental stress, as well as income inequalities and health inequities [4,8,15,16,42,45,48,49,52]. Accordingly, it is imperative that these groups are targeted in order to reduce health inequities.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of scholars argue that some Canadian policies towards ethno-racial minorities and racialized immigrants are not inclusive, and actually mask historical and contemporary realities of slavery, xenophobia, Othering, colonialism, and racism, which have been manifest in labour and citizenship policies 6,7 and have real consequences for wellbeing 8 and health. 9,10 In this paper, I raise the following research questions: What are the human rights consequences, and the potential health implications of banning religious symbols for Canadian workers in Quebec? Which ethnic or religious minorities are most affected by such policies?…”
Section: Introductionmentioning
confidence: 99%
“…Canadian studies of immigrants, racialized workers, and women suggest that these groups are often predisposed to high stress, chronic illness [ 32 , 33 , 34 ], and difficulties in managing domestic duties [ 35 ] due to work precarization [ 36 ], which adversely affects their health and well-being [ 33 ]. In addition, research has shown that in the care-work sector, many of these employees experience work hierarchies and strict divisions of labor [ 37 ], while utilizing various mechanisms to regulate emotional health [ 38 ].…”
Section: Discussionmentioning
confidence: 99%